Case report—Stumped: back pain in a cricketer - Lucas Lamote; Jo-Anne Heather Kirby (South African Journal of Sports Medicine, 2026)
A 19-year-old collegiate fast bowler presented with chronic low back pain that acutely worsened during a tournament. Examination suggested a mechanical origin, but plain radiographs showed subtle lucency at L5 and bilateral sacroiliac sclerosis. MRI was interpreted as bilateral sacroiliitis with effusion, raising concern for axial spondyloarthropathy. Laboratory tests, including HLA-B27, were unremarkable, and rheumatological evaluation did not support a seronegative spondyloarthropathy. Computed tomography ultimately demonstrated stress fractures with developing spondylolysis at L4 and L5. The player was managed conservatively with physiotherapy, core strengthening, and a phased return to sport, including modification of his bowling technique. Full return to sport was achieved at six months after initial presentation. This case highlights the diagnostic pitfalls of interpreting MRI findings in young athletes, where mechanical changes may mimic inflammatory sacroiliitis. CT remains a valuable adjunct in detecting lumbar stress fractures when MRI findings are equivocal.